2008
DOI: 10.1063/1.2919109
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and nonlinear optical characteristics of nanocomposites of ZnO–CdS

Abstract: In this article, we present the spectral and nonlinear optical properties of ZnO–CdS nanocomposites prepared by colloidal chemical synthesis. The optical band gap (Eg) of the material is tunable between 2.62 and 3.84 eV. The emission peaks of ZnO–CdS nanocomposites change from 385 to 520 nm almost in proportion to changes in Eg. It is possible to obtain a desired luminescence color from UV to green by simply adjusting the composition. The nonlinear optical response of these samples is studied by using nanoseco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(29 citation statements)
references
References 32 publications
5
24
0
Order By: Relevance
“…There is a change in absorption with the ZnO content and as the volume fraction of ZnO increases, the excitonic peak exhibits its signature. It is seen that the absorption edge corresponding to the nanocomposites gets red shifted and the exciton oscillator strength increases as a function of the ZnO content consistent with published reports [11,12]. The structure and size evolution of the nanocomposites may also have some relation with optical characteristics in addition to the composition and the study is in progress.…”
Section: Resultssupporting
confidence: 75%
“…There is a change in absorption with the ZnO content and as the volume fraction of ZnO increases, the excitonic peak exhibits its signature. It is seen that the absorption edge corresponding to the nanocomposites gets red shifted and the exciton oscillator strength increases as a function of the ZnO content consistent with published reports [11,12]. The structure and size evolution of the nanocomposites may also have some relation with optical characteristics in addition to the composition and the study is in progress.…”
Section: Resultssupporting
confidence: 75%
“…Larger particles have better optical limiting performance. The reverse saturable absorption, which is generally associated with a large cross section of absorption from excited levels, brings about optical limiting effects in colloidal solutions [22]. In this case, the optical limiting is due to two-photon absorption.…”
Section: Discussionmentioning
confidence: 99%
“…The band gap energy for the titanate nanotube was calculated to be 3.84 eV, which is closer to that of 3.87 eV of TiO 2 nanotubes reported by Bavykin et al [27]. Irimpan et al have reported that the absorption spectra of CdS shifted towards higher energies with respect to its bulk material in the CdS/ZnO nanocomposites [28]. Wang and co-workers also observed a blue shift of the absorption band edges of CdS nanoparticles after coupled with titanate nanotubes and ascribed it to the quantum size effect [20].…”
Section: Resultsmentioning
confidence: 79%